2020
DOI: 10.1038/s41598-020-69726-0
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of diet, deification, and death within ancient Egyptian mummified animals

Abstract: The clues to life and death of mummified animals can remain hidden beneath their wrappings. Developments in non-invasive imaging have enabled detailed study of their internal structures. Laboratory-based X-ray microcomputed tomography (microCT) and focussed imaging protocols permit smaller mummified remains, such as animals, to be studied at higher resolution. In this study, we use microCT to image three different animal mummies. Revealing the internal structures provides insights into their biography, the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Animal mummies have been investigated for centuries, and are unique in that they open a window into past religion, food, and even affection (McKnight et al, 2018;Ikram, Iskander, 2002). The scientific assessment of this valuable bioarchaeological resource, which dates from the Late to the Roman Empire periods (circa 664 BC -AD 395), can provide information on their nature, their manufacture, and even on the pathological conditions the animal suffered over its lifespan (Ikram, 2005a;2005b;Atherton-Woolham, McKnight, 2014;McKnight et al, 2015;Richardin et al, 2017;Johnston et al, 2020;Tamburini et al, 2021). In particular, crocodile mummies appear to be of great interest because they have been less studied as compared to other animals (De Cupere et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Animal mummies have been investigated for centuries, and are unique in that they open a window into past religion, food, and even affection (McKnight et al, 2018;Ikram, Iskander, 2002). The scientific assessment of this valuable bioarchaeological resource, which dates from the Late to the Roman Empire periods (circa 664 BC -AD 395), can provide information on their nature, their manufacture, and even on the pathological conditions the animal suffered over its lifespan (Ikram, 2005a;2005b;Atherton-Woolham, McKnight, 2014;McKnight et al, 2015;Richardin et al, 2017;Johnston et al, 2020;Tamburini et al, 2021). In particular, crocodile mummies appear to be of great interest because they have been less studied as compared to other animals (De Cupere et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Nos últimos 10 anos, a técnica de microtomografia de raios X, juntamente com os procedimentos computacionais de análise de imagens microtomográficas, tem sido usada para o estudo de variados tipos de materiais arqueológicos e com objetivos de pesquisa também diversos. Entre eles podem-se citar, por exemplo, alguns trabalhos de identificação de inclusões em artefatos de pedra e cerâmica (Obata, Miyaura & Nakano 2020;Ward et al 2019), caracterização de pastas cerâmicas (Kahl & Ramminger 2012;Lima et al 2007), objetos e decorações metálicas (Azeredo et al 2019;Machado et al 2019), análises de material ósseo humano e de outros animais e processos de mumificação (Beck et al 2012;Bello, De Groote & Delbarre 2013;Boschin et al 2015;Johnston et al 2020;Nava et al 2017), visualização de escritos antigos sobre suportes dobrados e frágeis (Stabile et al 2021), estudos de processos tafonômicos em sedimentos e artefatos (McBride & Mercer 2012;Ngan-Tillard et al 2015;Villagran et al 2019), e identificação de materiais arqueobotânicos (Calo et al 2019;Calo et al 2020;Coubray, Zech-Matterne & Mazurier 2010;Haneca et al 2012;Mizuno, Torizu & Sugiyama 2010;Murphy & Fuller 2017;Stelzner & Million 2015;Zong et al 2017) (Barron, Pritchard & Denham 2022;Barron & Denham 2018).…”
Section: Introductionunclassified
“…Recently, its importance and potential have become increasingly evident even when applied to other areas, such as industry and Cultural Heritage [1]. A growing number of authors have reported the successful use of CT as an efficient and non-destructive tool for the study of, for example, archaeological findings and works of art [2][3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%